Modeling of two-phase flow of high temperature geothermal production wells in the Yangbajing geothermal field, Tibet - Lei, Hongwu; Xie, Yingchun; Li, Jin; Hou, Xuewen (Frontiers in Earth Science, 2023)
Two-phase flow (flow of water in both liquid and gas phase, containing a non-condensable gas such as CO2) in the wellbore is one of the most important processes in the production performance and wellbore scaling evaluations of high temperature geothermal wells. This paper first describes the discharge tests in the Yangbajing geothermal field, Tibet. Next, a simple model for governing the two-phase flow in the presence of CO2 in the wellbore is constructed and a robust calculation method is presented. The model is applied to three production wells in the Yangbajing geothermal field. The results show that the velocity difference between the gas and liquid phase should be included in the model. Ignoring this difference (i.e., homogeneous model) would result in a significant deviation between measurements and the calculations. A drift flux model (DFM) describes the velocity difference, where the specifics of the particular model can have significant effects on the results for the pressure and temperature profiles in the wellbore. Three commonly used DFMs are compared to estimate their performance. The calculated wellhead pressure and temperature are in the range of 2-3 bar and 125-135 ℃ for all three wells at a production rate of about 20 kg/s. The estimated wellhead gas mass fraction is between 3% and 8%. Considering CO2 content, three different scenarios were evaluated, although the effect on the pressure and temperature profiles were limited. However, CO2 content has a much more significant effect on the flash depth, which is an important parameter for the estimation of calcite scaling.